Karakteristik Peternakan Kambing Rakyat di Kecamatan Biboki Anleu Kabupaten Timor Tengah Utara - Kosat, Aloysius Kristian; Atok, Marsiana Damaris; Sahala, Josua; Simamora, Ture; Fek, Wolfhardus Vinansius; Usboko, Novriana; Dethan, Agustinus Agung (Universitas Pahlawan Tuanku Tambusai, 2025)
The aim of this research is to determine the characteristics of goat breeders in Biboki Anleu District, North Central Timor Regency. This research was carried out from August to September 2024 in Biboki Anleu District, North Central Timor Regency. This research is a quantitative descriptive study using a survey method. The variables studied were the characteristics of goat breeders based on demographics, namely: characteristics based on age, gender, education level, ownership status, number of livestock ownership, breeder occupation, farming experience, number of family dependents, average monthly income and land ownership. The results of this research are the characteristics of goat farming in Biboki Anleu District, North Central Timor Regency. Based on age, most of the breeders are 20-55 years old, 60%, based on gender, generally 90% are men, the education of most breeders is elementary school graduates with a percentage of 78.3%, the livestock ownership status is mostly their own 100%, based on the number livestock ownership is mostly 1-5 heads, namely 63.3%, the main occupation of breeders is 86.6%, namely farmers, based on farming experience 38.3%, namely 3-5 years, number of dependents families mostly number 4-6 people, namely 51.7%, average monthly income 0-250,000, namely 50% and land ownership of more than 2 ha, namely 56.7%, the rearing system used by farmers in Biboki Anleu District is at most semi-intensive, as many as 40 people with a percentage of 66.6%, and the feed given to goats in Biboki Anleu District is mostly sago and forage given to 34 people with a percentage of 56.6%. The mating system applied in Biboki Anleu District, especially goats, is still mated naturally, the cages used in Biboki Anleu District are in the form of group cages, the cages are circular, which is a cage model that places several goats freely without being tied up, and for the health of the livestock handles itself using traditional medicine when the animals are sick.